Energy metabolism and muscle activation heterogeneity explain VO2 slow component and muscle fatigue of cycling at different intensities - do Nascimento Salvador, P. C.; Nascimento, E. M. F.; Antunes, D.; Guglielmo, L. G. A.; Denadai, B. S. (Experimental Physiology, 2023)
New Findings